THE EFFECT OF MOTIVATION, DISCIPLINE, AND THE WORKING ENVIRONMENT ON EMPLOYEE’S JOB SATISFACTION - Stepanus Dedy Deomedes; Muhammad Adam (Jurnal GeoEkonomi, 2021)
This study aims to determine the effect of work motivation, discipline and work environment on job satisfaction of the employees of Balikpapan Local water Supply Company (PDAM). This research was conducted on the employees of the Balikpapan PDAM. The sample sizes taken were 187 employees. The results show that there is simultaneous effect of work motivation, discipline, and work environment to job satisfaction. Work motivation partially has a positive and significant effect on job satisfaction. Discipline partially has a positive and significant effect on job satisfaction and the work environment partially has a positive and significant effect on job satisfaction. The most dominant influence on job satisfaction is discipline.